Advancement of Proton-Conducting Solid Oxide Fuel Cells and Solid Oxide Electrolysis Cells at Idaho National Laboratory (INL). (10th July 2019) - Ding, Hanping; Wu, Wei; Ding, Dong
Abstract : Proton conducting ceramics have been considered as a strategic material system used in solid oxide fuel cells and solid oxide electrolysis cells for electricity generation and hydrogen production. The high proton conductivity of protonic electrolyte and rapid development of robust electrode materials have significantly promoted the reduction of feasible operating temperature to intermediate temperature range (400~600 °C), which can attribute to favorable technical and economic advantages when they are compared with conventional oxide-ion conducting electrolyte based solid oxide cell system. In the past few years, Idaho National Laboratory has been devoted to developing advanced electrolyte and electrode materials R&D, diverse manufacturing capability, and expanding evaluation facility for these applications, aiming to further improve performance, stability and manufacturing cost. There are some remarkable accomplishments achieved on electrode engineering, electrolyte optimization, new material down-selection and large-scale cell fabrication in Idaho National Laboratory.